The fall out of redemption : writing and thinking beyond salvation in Baudelaire, Cioran, Fondane, Agamben, and Nancy /: writing and thinking beyond salvation in Baudelaire, Cioran, Fondane, Agamben, and Nancy. (2015 copyright 2015) - Acquisto, Joseph, 1975-
No abstract available